The first theologians a study in early Christian prophecy - Gillespie, Thomas W., 1928- (Grand Rapids, MI Eerdmans, 1994)
Includes bibliographical references.
Keywords: Prophecy -- Christianity -- History of Doctrines -- Early church, ca. 30-600.; Theology -- History -- Early church, ca. 30-600.